Monitoring the agri-food system in Myanmar: Agricultural equipment supply chain – November 2024 - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
Agricultural Equipment Supply Chain – November 2024 This research note presents the impacts of recent economic disruptions on Myanmar’s agricultural equipment supply chain, based on a phone survey of agricultural equipment vendors (AEVs) and repair service providers (RSPs) conducted in November 2024. Key Findings • Businesses face multiple disruptions, including transport restrictions, high costs, fluctuating exchange rates, and limited electricity and fuel. Safety concerns during transport were reported by 64 percent of RSPs and 26 percent of AEVs. • Availability of agricultural machinery has declined significantly from last year, with reductions in two-wheel tractors (84 percent), four-wheel tractors (78 percent), and threshers (75 percent) reported by AEVs. This decline is likely driven by reduced demand, mobility restrictions, and high transportation costs. • Availability and sales of spare parts and attachments are relatively stable, reflecting a shift towards maintaining and upgrading existing machinery. Combine harvesters and threshers show some resilience, potentially linked to agricultural labor shortages. • Despite significant disruptions, most businesses report financial stability. While revenues have declined, businesses show resilience to recent shocks. RSPs appear to be benefiting from the growing demand for repair and maintenance services. Recommended Actions • Implement training programs that improve the availability and skills of mechanics to support RSPs as farmers focus on maintaining and upgrading their machinery. • Train operators in proper use and maintenance practices, helping to extend the lifespan of machinery and reduce repair needs. • Facilitate the expansion of domestic manufacturers of spare parts and attachments to improve the quantity, quality and variety of parts and attachments available. • Ensure consumers have access to credit with favorable terms, enabling them to purchase machinery and spread repayment over time in line with economic conditions. • Extend and expand the expedited approval of import licenses, and reduce other import barriers, for agricultural equipment and raw material needed by domestic producers to ensure stable supply and support of local manufacturing capabilities.